Long term outcomes of Murray Valley encephalitis cases in Western Australia - what have we learnt? - Selvey, Linda; Speers, D.; Smith, D. (2015)
BACKGROUND: Murray Valley encephalitis virus (MVEV) is a mosquito-borne flavivirus that causes encephalitis in some cases of infection. It is endemic in Northern Australia and cases occasionally occur in South Eastern Australia. The long-term sequelae of MVEV infection have not previously been well-described. AIM: To investigate the long-term sequelae of MVEV infection. METHODS: This was a descriptive case series of all clinical MVEV infections using data linkage and standard surveys. Hospital admissions, emergency department, psychiatric outpatients and mortality data were obtained. We attempted to follow up all 53 cases of MVEV clinical infection that occurred in WA from 1978 to 2011 inclusive. Two cases opted out of the study. RESULTS: We followed up 39 surviving cases. Seven of the nine with paralysis or paresis were under five years and they fared worse than other patients, requiring lengthy hospitalisation (median duration 133 days). Two died due to complications of quadriplegia following a total of 691 days in hospital. Nine surviving patients, including two with non-encephalitic illness, required care for depression and other psychiatric conditions following MVEV infection. Two patients who were discharged with neurological sequelae had no further documented hospital occasions of service but reported ongoing challenges with cognitive dysfunction and inability to work. CONCLUSIONS: This is the first study of long-term outcomes of Murray Valley Encephalitis that included cases with no obvious sequelae at discharge. In spite of the small numbers involved, the study demonstrated the significant medical and social burden due to MVEV in Australia.